The Causes of Low Female Literacy Rates in Developing African and Asian Countries: The Role of Government in Driving Change - Hungwe, Rivaldo; Khan, Farah (Innovare Journal of Education, 2025)
The challenge of low female literacy rates is a matter of concern in the developing countries of Africa and Asia, which limits women’s empowerment and affects social and economic development. The article investigates the main reasons behind poor literacy levels, which are caused by social-economic challenges together with cultural or religious obstacles, insufficient educational facilities, and unsafe school conditions. Relevant education statistics such as levels and school attendance dropout rates and expenditure information were obtained from respected organizations such as United Nations Educational, Scientific and Cultural Organization (UNESCO) and the World Bank. Lowering gender discrepancies in literacy needs coordinated support between state authorities, and community organizations, and international institutions. The proposed recommendations support free education through law enforcement as well as financial rewards to female students and better educational facilities and teacher training for gender-responsive practices. Such actions play a critical role in reaching the United Nations Sustainable Development Goals as well as supporting social growth involving everyone.